2006
DOI: 10.1007/s00426-006-0074-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulatory strategy and executive control: implementation intentions modulate task switching and Simon task performance

Abstract: Two tasks where failures of cognitive control are especially prevalent are task-switching and spatial Simon task paradigms. Both tasks require considerable strategic control for the participant to avoid the costs associated with switching tasks (task-switching paradigm) and to minimize the inXuence of spatial location (Simon task). In the current study, we assessed whether the use of a self-regulatory strategy known as "implementation intentions" would have any beneWcial eVects on performance in each of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 39 publications
3
65
0
Order By: Relevance
“…As the emotional reactivity under scrutiny (i.e., disgust and spider fear) can be assumed to carry features of automaticity, these mere goal intentions should turn out to be quite ineffective. At least, that is what has been suggested by prior implementation intention research on the control of automatic behavioral and cognitive responses; there, mere goal intentions consistently failed to have an effect (e.g., A.-L. Cohen et al, 2008;Holland et al, 2006). Study 1: The Self-Regulation of Disgust…”
Section: Regulating Emotional Reactivity By Implementation Intentionsmentioning
confidence: 68%
“…As the emotional reactivity under scrutiny (i.e., disgust and spider fear) can be assumed to carry features of automaticity, these mere goal intentions should turn out to be quite ineffective. At least, that is what has been suggested by prior implementation intention research on the control of automatic behavioral and cognitive responses; there, mere goal intentions consistently failed to have an effect (e.g., A.-L. Cohen et al, 2008;Holland et al, 2006). Study 1: The Self-Regulation of Disgust…”
Section: Regulating Emotional Reactivity By Implementation Intentionsmentioning
confidence: 68%
“…Although these conclusions have to remain speculative at this point, there is evidence that implementation intentions may cause some attention-related costs (Cohen et al 2008). Ellis and Freeman (2008) indicate that the assumption that implementation intentions in general use relatively few attentional resources is potentially oversimplistic.…”
Section: Discussionmentioning
confidence: 99%
“…First, encoding an implementation intention may lead to a heightened accessibility of the situational cue indicating the appropriate moment to initiate the planned action (either by increased activation or a reduced threshold), therefore helping to facilitate the detection of that cue in the environment. Here it is assumed that they create a state of perceptual readiness (Cohen and Gollwitzer 2008). Second, implementation intentions may increase the likelihood of a strong association between the cue and the associated memory trace, resulting in the memory trace for the intended action being delivered automatically to consciousness (Ellis and Freeman 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, implementation intentions are thought to represent an efficient mechanism for goal attainment. By contrast, goal intentions (i.e., representations of overarching goals rather than specific cue-action links) may be less effective because they are more dependent on self-initiated behavior (Cohen, Bayer, Jaudas, & Gollwitzer, 2008;Gollwitzer & Sheeran, 2006; see also Achtziger, Gollwitzer, & Sheeran, 2008, for evidence that implementation intentions may in addition be triggered by internally generated cues such as craving for chocolate). In the cognitive neuroscience of prospective memory, it has been suggested that rostral prefrontal cortex (approximating BA 10) plays a crucial role due to the requirement to flexibly mediate the attentional balance between internally represented information (such as delayed intentions) and externally derived perceptual information relevant to the ongoing task (Burgess et al, 2008).…”
Section: Environmental Cueing and Implementation Intentionsmentioning
confidence: 99%